Aktivitas Antidiabetes Infusa Buah Mengkudu (Morinda Citrifolia L.) pada Mencit Jantan terinduksi Aloksan - Mulki, Munir Alinu; Amelia , Tiara Cinta (Journal of Pharmaceutical and Sciences, 2026)
Noni (Morinda citrifolia L.) is traditionally consumed for diabetes, yet in vivo evidence for water-based infusion remains limited. This study aimed to evaluate the antihyperglycemic effect of a standardized noni fruit infusion in alloxan-induced male mice. Dried fruit simplicia were quality-controlled according to the Indonesian Herbal Pharmacopoeia. Mice were induced with alloxan (140 mg/kg, i.p.) and randomized (n=5/group) to vehicle (0.5% Na-CMC), metformin (1.3 mg/20 g BW), or noni infusion at low (103), normal (123), or high (144 mg/20 g BW) for 21 days in two divided doses per day. Fasting blood glucose was measured at baseline, day 0, and days 7, 14, and 21. Paired t-tests assessed within-group changes, while between-group comparisons used one-way ANOVA with Levene’s test (Tukey HSD) and Welch ANOVA as sensitivity analysis. Phytochemical screening indicated alkaloids, saponins, triterpenoids, and flavonoids. All groups showed significant reductions from day 0 to day 21 (p<0.05). From day 0 to day 14, the normal-dose infusion decreased glucose by 45.7% (172.8 to 93.8 mg/dL), compared with 33.3% for metformin (134.0 to 89.4 mg/dL). By day 21, reductions were 48.3–49.6% in the normal/high-dose infusion groups and 36.4% with metformin. Between-group differences were evident at days 7 and 14 but not at day 21 (p>0.05). Standardized noni infusion exhibits antihyperglycemic activity in the alloxan model; confirmation of mechanisms, additional metabolic endpoints, and subchronic safety evaluation are required before clinical relevance can be inferred.